STRATEGIC APPROACH TO THE DEVELOPMENT OF THE “COMPETITIVE POTENTIAL OF REGIONS” IN THE POST-WAR PERIOD OF UKRAINE - Lipentsev, Andriy; Beltiukov, Ruslan (Public Management and Policy, 2025)
This article analyzes the formation of a strategic approach to developing the competitive potential of regions in post-war Ukraine, presenting the key indicators for realizing regional competitive advantages. Based on this analysis, a strategic model for the development of regional competitive potential is proposed, which provides for the expansion of the state’s resource capabilities aimed at stabilizing the processes of national socio-economic recovery. Regions are characterized as entities embodying the “key success factors” for the state’s economic reconstruction in the post-war period, serving as providers of innovation and adaptability to new conditions. The study articulates the critical prerequisites necessary to achieve desired dynamics of socio-economic development and establish a crucial balance between internal resources and external threats that lead to the deconstruction of economic reality during the post-war phase. It is proven that any deviation by regions from integrating a multi-component strategy for developing their competitive potential will result in a rollback of their competitiveness and failure to build up their resource capabilities. The paper develops a toolkit for managing inter-regional competition to stabilize socio-economic development processes and expand the institutional capacity of regions, thereby strengthening their competitive positions within the national market. The essence of this strategic development is characterized through the lens of expanding regional competitive capabilities toward the creation of high-tech products, leading to the identification of the concept of “coordinated development of regional competitive potential”. This concept involves maximizing regional internal and external opportunities by creating “strategies” that enhance their competitiveness within national and global markets. Finally, a methodology for developing a strategic approach is proposed, which involves the implementation of long-term projects and programs aimed at restoring the stabilization dynamics of regional functioning and, consequently, introducing effective methods for creating sustainable competitive advantages based on mobile indicators of growth in economic activity.